Investigation of the relationship between authoritarian personality and marriage readiness of emerging adult women - Utami, Yasmin Adlina Heraputri; Muttaqin, Darmawan; Wahyuningsih, Sri (University of Muhammadiyah Malang, 2023)
Emerging adulthood will experience a phase of self-exploration and enter married life. Therefore, individuals must have an authoritarian personality to adapt to changing roles and rules. Authoritarian personality supports individuals’ married life because they must be submissive and obey the rules, values, norms, etc. This research investigated the relationship between authoritarian personality and marriage readiness in emerging adult women (Respondents number (N) =196). The technique employed was purposive sampling. The research instruments used the Authoritarian Personality Scale and the Marriage Readiness Scale. This study applied the Pearson Product-Moment hypothesis testing method. The results revealed a positive correlation between authoritarian personality and marriage readiness (r=.415, p=0.000). Besides, authoritarian personality was also correlated with all aspects of marriage readiness. For individuals in emerging adulthood, it is necessary to understand that a submissive and obedient attitude can help them to be better prepared to face a new life, namely marriage.